Cannabis-like activity of Zornia latifolia Sm. detected in vitro on rat cortical neurons: major role of the flavone syzalterin - Alloisio, Susanna; Clericuzio, Marco; Nobile, Mario; Salis, Annalisa; Damonte, Gianluca; Canali, Claudia; Fortuna-Perez, Ana Paula [UNESP]; Cornara, Laura; Burlando, Bruno (Taylor & Francis, 2020)
Zornia latifolia is a plant suspected to possess psychoactive properties and marketed as a marijuana substitute under the name ‘maconha brava’. In this study, the effects of fractions obtained from a 2-propanol extract of aerial portions of the plant were determined by multielectrode array (MEA) analyses on cultured networks of rat cortical neurons. Lipophilic (ZL_lipo, mainly containing flavonoid aglycones), and hydrophilic (ZL_hydro, mainly containing flavonoid glycosides) fractions were initially obtained from the raw extract. ZL_lipo significantly inhibited mean firing rate (MFR) and mean bursting rate (MBR) of MEA recordings, while ZL_hydro induced no inhibition. Column chromatography separation of ZL_lipo yielded five fractions (ZL1-ZL5), among which ZL1 induced the strongest MFR and MBR inhibition. NMR and HPLC-MS analyses of ZL1 revealed the prevalence of the common flavonoids genistein (1) and apigenin (2) (in about a 1:1 ratio), and the presence of the rare flavone syzalterin (6,8-dimethylapigenin) (3) as a minor compound. Exposures of MEA to apigenin and genistein standards did not induce the MFR and MBR inhibition observed with ZL1, whereas exposure to syzalterin standard or to a 1:9 mixture syzalterin-genistein induced effects similar to ZL1. These inhibitory effects were comparable to that observed with high-THC hashish, possibly accounting for the plant psychoactive properties. Data indicate that Z. latifolia, currently marketed as a free herbal product, should be subjected to measures of control. In addition, syzalterin showed distinctive pharmacological properties, opening the way to its possible exploitation as a neuroactive drug.
Keywords: Flavonoids; hashish; multielectrode array; psychoactive metabolites; smart drugs